2020
DOI: 10.3390/jcm9072043
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Effects of Everolimus in a Human Granuloma Model

Abstract: Mycobacterium tuberculosis (M. tb) has been historically and is currently a threat to global public health. First-line antibiotics have been effective but proven to be burdensome as they have many potential adverse side effects. There has been a recent increase in the number of active tuberculosis (TB) cases due to a prevalence of multidrug and extensively drug-resistant strains of M. tb, and an increasing number of highly susceptible people such as those with Type 2 Diabetes (T2DM) and human immunodeficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 43 publications
0
41
2
Order By: Relevance
“…Lysate, 6h www.nature.com/scientificreports/ On the other hand, mROS were shown to stimulate autophagy, which is an important macrophage defense mechanism against intracellular bacterial pathogens including B. cenocepacia 59,65,72 . The activation of autophagy promotes the clearance of B. cenocepacia 12 , Legionella pneumophila 18 , Listeria monocytogenes 73 , and Mycobacterium tuberculosis 74 . Increased mROS production which activates autophagy improves the clearance of Mycobacterium tuberculosis 75 , Streptococcus pneumoniae 76 and Listeria monocytogenes 77 .…”
Section: Lc3i Lc3iimentioning
confidence: 99%
“…Lysate, 6h www.nature.com/scientificreports/ On the other hand, mROS were shown to stimulate autophagy, which is an important macrophage defense mechanism against intracellular bacterial pathogens including B. cenocepacia 59,65,72 . The activation of autophagy promotes the clearance of B. cenocepacia 12 , Legionella pneumophila 18 , Listeria monocytogenes 73 , and Mycobacterium tuberculosis 74 . Increased mROS production which activates autophagy improves the clearance of Mycobacterium tuberculosis 75 , Streptococcus pneumoniae 76 and Listeria monocytogenes 77 .…”
Section: Lc3i Lc3iimentioning
confidence: 99%
“…Increased delivery of M. tuberculosis to such phagolysosomes mediated through pharmacologic induction of autophagy may be an additional means by which mTOR inhibition could augment pyrazinamide efficacy. Consistent with this, a recent study using an in vitro granuloma model found that everolimus augmented pyrazinamide activity to a more significant extent than its effects on isoniazid activity (24). While we cannot exclude the possibility that co-administration of CC214-2 reduced the exposure to one or more components of the BPaL regimen through an adverse drug-drug interaction, this is unlikely because CC214-2 is not a substrate or inducer of CYP 3A4 or P-gp and was administered separately in time from the antimicrobials to avoid interference with absorption.…”
Section: Discussionmentioning
confidence: 63%
“…The widely discrepant effects observed between the mTOR inhibitors evaluated here may be attributable to the properties and selectivity of the mTOR inhibitors. Although rapamycin and especially analogs such as everolimus have been explored (7, 12, 14, 24, 25) for use as adjunctive HDT for TB, to our knowledge, they have not been studied previously with combination chemotherapy in a mouse model of TB. Due to their effects on the AKT/mTOR pathway and autophagy, they only partially inhibit mTORC1 and do not inhibit mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…The development of combinatorial therapeutic modalities with the involvement of additional antimycobacterial agents and conventional che-motherapy indicated a breakthrough in therapeutic interventions for tuberculosis, especially in cases of multidrugresistant tuberculosis. Among the recent drug discoveries, new "host-targeted" adjunct therapeutic strategies have emerged [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%